2019
DOI: 10.1097/jnc.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Moving to Another World: Understanding the Impact of Clinical Trial Closure on Research Participants Living With HIV in Uganda

Abstract: The authors report no real or perceived vested interests related to this article that could be construed as a conflict of interest. research, for allowing us to undertake the research on their premises. We greatly thank the staff of these institutions for tirelessly contributing toward the recruitment process of the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In low income settings such as Uganda, it is a reality that most aspects of healthcare provided in a clinical trial context (in research clinics) is usually significantly better than public sector provision [1,2]. Once withdrawn from such care at trial closure, trial participants can experience feelings of loss and other negative effects [3,4]. Studies have shown that these negative effects include issues such as psychological stress related to loss of quality care and loss of material benefits, worries about how to access care after trial exit, challenges associated with linkage to care facilities and challenges with meeting treatment and transport costs [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low income settings such as Uganda, it is a reality that most aspects of healthcare provided in a clinical trial context (in research clinics) is usually significantly better than public sector provision [1,2]. Once withdrawn from such care at trial closure, trial participants can experience feelings of loss and other negative effects [3,4]. Studies have shown that these negative effects include issues such as psychological stress related to loss of quality care and loss of material benefits, worries about how to access care after trial exit, challenges associated with linkage to care facilities and challenges with meeting treatment and transport costs [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Once withdrawn from such care at trial closure, trial participants can experience feelings of loss and other negative effects [3,4]. Studies have shown that these negative effects include issues such as psychological stress related to loss of quality care and loss of material benefits, worries about how to access care after trial exit, challenges associated with linkage to care facilities and challenges with meeting treatment and transport costs [1,2,4]. While many researchers appear to pay much attention about the care obligation to research participants during trial conduct, less importance is attached to the post-trial period and therefore less effort is put in managing this phase of trial conduct [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, areas such as recruitment, informed consent, standards of care during research, and monitoring and management of adverse effects during trial conduct receive greater attention than the issue of post-trial obligations (Nalubega and Evans, 2015). Recent research suggests that trial closure can be a stressful time for trial participants and that additional support for participants may be required during the trial closure period (Nalubega et al, 2019). Research ethical debates have, therefore, started to focus on post-trial care.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in the field of HIV have recommended the need to address a range of post-trial care needs of research participants including ensuring continued access to required HIV treatments, psychosocial support and other services, (Cho et al, 2018;Nalubega et al, 2019Nalubega et al, , 2021Vallely et al, 2009). Despite these recommendations, a gap in research regulation appears to exist whereby available policy guidelines are too generic and do not emphasise key aspects of research ethics which appear essential to some stakeholders (Kwagala et al, 2010).…”
Section: Introductionmentioning
confidence: 99%